Gender mainstreaming : commonwealth strategies on politics, macroeconomics and human rights (Commonwealth Secretariat LondonGB, 1988)
Suggests strategies for increasing women's participation in politics, and offers options for the integration of gender issues into national budgetary policies and procedures. Provides 5 tools for effecting the integration. Examines women's rights, focusing on strategies for combating violence against women, and sexual exploitation of the girl-child, especially in Asia and Africa.
Located in the Learning Resource Centre